Correlating physical activity and quality of life of healthcare workers - Saridi, Maria; Filippopoulou, Theodora; Tzitzikos, Georgios; Sarafis, Pavlos; Souliotis, Kyriakos; Karakatsani, Despoina (My University, 2019)
The purpose of the present study was to investigate healthcare workers' physical exercise levels linked to their quality of life. Healthcare workers' from all departments of a General hospital participated in the study. The instruments used for data collection regarding quality of life and physical exercise (Short Form Health Survey (SF-36) and International Physical Activity Questionnaire-short form).
Keywords: Healthcare worker; Physical activity; Physical exercise; Quality of life